Instructional staff employment in higher education: 2013 - Schulman, Steven, author (Colorado State University. Libraries, 2019)
This report shows instructional staff employment -- tenured faculty, tenure track faculty, part-time non-tenure track faculty, full-time non-tenure track faculty, non-faculty instructors and graduate teaching assistants -- at every college and university in the U.S., as well as summary tables and charts. They include two measures of contingency, the percent of faculty off the tenure track (the "faculty non-tenure track rate") and the percent of instructional staff off the tenure track (the "contingency rate").
Keywords: academic employment; instructional staff; faculty; higher education